Asociación entre anestesia regional e hipotermia intraoperatoria en cirugías traumatológicas de miembro inferior - Gutiérrez García, Luis Felipe (2023)
A study will be carried out in order to determine the association between regional anesthesia and intraoperative hypothermia in lower limb trauma surgeries; through a study whose design will be analytical, observational, prospective cohort; the population will be comprised of patients exposed to arthroplasty and treated at the hospital who meet the selection criteria; In the statistical analysis, the measures of frequency and association will be found. First, the incidence of cases in the exposed and unexposed will be determined, then the relative risk association measures.